Formulation and antioxidant activity test of sea kale cream (Ipomoea pescaprae) with DPPH (1.1-diphenyl-2-picrylhydrazyl) method - Delladari Mayefis; Habibie Deswilyaz Ghiffari; Ristama Sastra Yoseva Manurung; Desi Maniarti Gusmali (Institute of Computer Science (IOCS), 2023)
Sea kale (Ipomoea pescaprae) is one of the Indonesian medicinal plants used by the community to treat inflammation, diuretic disorders, and pain in gonorrhea. Sea kale can also be used as a source of natural antioxidants that can counteract free radicals. Sea kale contains secondary metabolites such as alkaloids, flavonoids, tannins and saponins. This study aims to determine the antioxidant activity of cream preparations containing sea kale leaf extract against DPPH(1.1-diphenyl-2-picrylhydrazyl) and to find out what concentration of sea kale leaf extract cream has the highest activity as an antioxidant. Sea kale (Ipomoea pescaprae) was extracted by maceration method using methanol solvent and then preparations were made in cream form using various extract concentrations, namely 5%, 7.5% and 10%. Furthermore, evaluation of cream preparations was carried out, namely organoleptic test, homogeneity test, spreadability test, pH test, viscosity test and cream type test. Determination of antioxidant activity was carried out using the DPPH method and vitamin C as a comparison by calculating the IC50 value. IC50 results obtained in formula I with 5% extract of 237.63 ppm (Medium), formula II with 7.5% extract of 91.83 ppm (Strong) and formula III with 10% extract of 7.32 ppm (Very strong). Meanwhile, the positive control for vitamin C had an IC50 value of 5.33 ppm (very strong). Formula III is the best formula that has very strong antioxidant activity.